The Securities Market in Ukraine: Theoretical Aspects of Historic Development - S. S. ZALIUBOVSKA; Yu. B. KOLUPAYEV; К. R. TOKАREVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article sums up a review of theoretical approaches to the interpretation of economic categories “securities market” and “stock market” and a chronological analysis of the stock market development in independent Ukraine.It is shown that two general approaches to the interpretation of the above categories exist, legislative and scientific. The latter one can, in turn, be subdivided into narrower approaches: segment approach, with securities market treated as a part of the capital market or financial market; functional approach, with securities market seen as a floor for sales and purchase of securities; normative approach, with securities market addressed as a sophisticated mechanism used to set legal and economic relations between business entities; logical approach, with securities market considered as a set of transaction mechanisms. The authors’ definition of the securities market is proposed: a segment of the financial market, on which interactions between various market actors take place, related with issuance, purchase and sales of securities that have value, circulate freely and certify the relations of co-ownership or lending, with the purpose of effective distribution and rational allocation of financial resources in the socio-economic area of a country with due account for the society’s interests and needs.The authors’ chronology of the securities market development in Ukraine is proposed, in which six phases are distinguished. The first phase is “reappearance” (1990). The second phase is “formation” (1991–1994), falling upon radical market-driven transformation in the Ukrainian economy. The third phase is “development” (1995–1999): search of the effective owners on the boosting market, setting up a system for control over sales and purchase of securities, creation of investment funds, financial and industrial companies and private pension funds. The fourth phase is “improvement” (2000–2002): creating a system for information support for circulation of securities issued in non-documentary form, and computer software for operating the State registers. The fifth phase is “recovery” (2003–2006): gradual decline of crisis tendencies in the economy along with the recover at the securities market.  The sixth phase is “financial globalization” (from 2007 and on). This approach enables to investigate the securities market dynamics over 1991–2018 and give detailed descriptions of each phase with emphasis on core historic event in each.